Design and Performance Analyses of V-OFDM Integrated Signal for Cell-Free Massive MIMO Joint Communication and Radar System - Cao, Yu; Yu, Qi-Yue (IEEE systems journal, 2023)
Cell-free massive multiple-input-multiple-output (MIMO) network is appealing since the distributed architecture provides spatial diversity to reduce the large-scale fading effect significantly. This article presents a cell-free massive MIMO joint communication and radar (JCR) system, which simultaneously provides qualified communication and robust target detection services. We apply vector orthogonal frequency division multiplexing integrated signals into the proposed cell-free JCR systems, which can achieve well-behaved performances, e.g., high spectral efficiency, superior detection resolution, and accurate latency/Doppler estimation results. Moreover, a low-complexity alternative grid searching method is designed, and the latency and Doppler estimation rates of the proposed system are derived, which gives the lower bounds of estimation performance. The beamforming weights and power allocation results are calculated by using the alternative Lagrange multiplier algorithm. Simulation results demonstrate that the proposed system outperforms the classical centralized JCR case in terms of ambiguity function, bit error rate, false alarm, and detection probabilities, verifying the efficiency of the proposed system.